Preparation and evaluation of 2-methoxyestradiol-loaded pH-sensitive liposomes - Suna He; Bowen Wang; Runfang Zhang; Huanhuan Zhou; Qian Yang
The development and clinical application of 2-methoxyestradiol (2-ME) as a new type of antitumor drug are limited due to its poor solubility, rapid metabolism in vivo, and large oral dosage. 2-ME-loaded pH-sensitive liposomes (2-ME-PSLs) was prepared containing the lipids, Lipoid E-80 (E-80), cholesteryl hemisuccinate (CHEMS), and cholesterol (CHOL) via thin-film ultrasonic dispersion. First, preparation conditions of 2-ME-PSLs were optimized by orthogonal test. Then 2-ME-PSL was characterized, and the release behavior and stability of 2-ME-PSL in vitro were evaluated. The optimal preparation conditions for 2-ME-PSLs were as follows: 2-ME : E-80+CHEMS 1:15; CHOL : E-80+CHEMS 1:5; ultrasonication time 20 minutes. The mean particle size, PDI, zeta potential, and entrapment efficiency (EE) of 2-ME-PSLs were 116 ± 9 nm, 0.161 ± 0.025, −22.4 ± 1.7 mV, and 98.6 ± 0.5%, respectively. As viewed under a transmission electron microscope, 2-ME-PSLs were well dispersed and almost spherical. They exhibited significant pH-sensitive properties and were fairly stable when diluted with a physiological solution. In conclusion, 2-ME-PSLs were successfully prepared and possessed a favorable pH sensitivity and good dissolution stability with a normal solution.